The Influence of Product Assortment, Price Perception, and Service Quality on Purchase Decisions (A Study of M.G.S Collection Customers at Cipulir Market, South Jakarta) - Marlina, Alia; Vildayanti, Rina Ayu (Jurnal Multidisiplin Sahombu, 2025)
This study examines how product assortment, price perception, and service quality shape purchase decisions in an apparel retail context. Using a survey of store customers, we test a conceptual model grounded in consumer value and service quality theory. Measurement reliability and validity were assessed, and assumptions for regression analysis were satisfied. The findings indicate that a broader and more coherent assortment enhances perceived choice and increases the likelihood of purchasing. Positive price perception, reflected in fairness and value, strengthens purchase intentions. Service quality, especially responsiveness and assurance, exerts a direct effect on decisions while also amplifying the roles of assortment and price. The integrated model explains a substantial share of decision variance and offers practical guidance: align assortment breadth with target segments, communicate transparent pricing, and standardize service routines. The study contributes contextual evidence from a traditional market setting and recommends future work on loyalty outcomes and digital touchpoints journeys.